Early Childhood Science Education from 0 to 6: A Literature Review - Gillian O'Connor; Glykeria Fragkiadaki; Marilyn Fleer; Prabhat Rai (MDPI AG, 2021)
Over the past three decades, our understanding of science learning in early childhood has improved exponentially and today we have a strong empirically based understanding of science experiences for children aged three to six years. However, our understanding of science learning as it occurs for children from birth to three years, is limited. We do not know enough about how scientific thinking develops across the first years of life. Identifying what we do know about science experiences for our youngest learners within the birth to three period specifically, is critical. This paper reviews the literature, and for the first time includes children in the birth to three period. The results are contextualised through a broader review of early childhood science education for children aged from birth to six years. Findings illustrated that the empirical research on science concept formation in the early years, has focused primarily, on children aged three to six years. The tendency of research to examine the process of concept formation in the birth to three period is also highlighted. A lack of empirical understanding of science concept formation in children from birth to three is evident. The eminent need for research in science in infancy-toddlerhood is highlighted.